CD52, CD22, CD26, EG5 and IGF-1R expression in thymic malignancies. (June 2017) - Remon, J.; Abedallaa, N.; Taranchon-Clermont, E.; Bluthgen, V.; Lindsay, C.R.; Besse, B.; Thomas de Montpréville, V.
Highlights: Immunohistochemistry is a valid tool to identify overexpression of predictive markers. EG5 expression was significantly higher in thymic carcinomas. Agents targeting CD52, CD 22, CD26 and EG5 could be further explored in TET patients. Abstract: Background: Thymic epithelial tumours are rare cancers for which new treatment options are required. Identification of putative predictive markers is important for developing clinical trials. We studied the expression of five putative predictive biomarkers, potentially actionable by approved experimental drugs. Methods: CD52, CD22, CD26, EG5, and IGF-1R expression were investigated by immunohistochemistry in formalin-fixed surgical samples of thymic epithelial tumour patients. All samples containing 10% positive epithelial tumour cells, independent of tumour cell intensity, were considered as positive. Correlation with histological subtype was performed. Results: 106 surgical samples (89 thymomas, 12 thymic carcinoma, and 5 thymic neuroendocrine tumours) were evaluated. Overall, CD52, CD22, CD26, EG5 and IGF-1R expression was observed in 7%, 42%, 25%, 42% and 77% of samples, respectively. CD52 expression was more frequent in B2 and B3 thymoma. All TET subtypes stained for CD22, mainly AB thymoma (68%). CD26 expression also correlated with AB thymoma (68%), and A thymoma (50%) subtype, while IGFR1 was the most common marker expressed by thymic carcinoma samples (92%), followed by EG5 (60%). Only EG5 expression was significantly higher in thymic carcinomas than in thymomas (75% vs. 38%, p = 0.026). Conclusions: Our data were consistent with a previous study of IGF-1R expression. Based on their expression, activity of agents targeting CD52, CD 22, CD26 and EG5 could be further explored in TET patients.